Once a land of big wild rivers: specialism is context-dependent for riparian snails (Pulmonata: Valloniidae) in central Europe - Altaba, Cristian R. (Biological journal of the Linnean Society, 2015)
Specialist species may be perceived as such because of their narrow ecological requirements, but this may be context‐dependent. The genus Vallonia (Gastropoda Pulmonata: Valloniidae) includes widespread generalist species and also two specialists endemic to Central Europe: Vallonia suevica, restricted to warm, wet meadows and riverbanks subject to seasonal flooding; and Vallonia declivis, living only in wet to humid meadows, riverbanks, and reedbeds. Both have experienced dramatic declines; as is the case with many land snails, their global conservation status has been underestimated: these species are Critically Endangered. Other congenerics are probably dispersed by birds. In contrast, the distributions of these meadow specialists appear to be the outcome of their strictly riparian habitat coupled with dispersal by fish. Thus, they have tracked drainage changes through the Pleistocene from their origin in the floodplain uplands of the Danube biodiversity hotspot in the Pliocene. Natural dispersal mechanisms have been disrupted, and riparian and river ecosystems have been destroyed throughout Europe. This has led big‐river specialist molluscs and their associated fishes to the brink of extinction. The notion of specialism thus depends on the ecological context; it is useful to stress their non‐invasive character, current restriction to scarce habitats, and evolution under quite different conditions. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.